2006
DOI: 10.1080/00420980500533133
|View full text |Cite
|
Sign up to set email alerts
|

High-rise Living in Singapore Public Housing

Abstract: Summary. In recent years, amid the debates of sustainable development and urban compactness, there has been a widening interest to reintroduce high-rise living in cities. Several European cities including London and Manchester are once again building high-rise housing as part of their urban housing strategy. Elsewhere, in Asia, Hong Kong and Singapore are distinguished by their high-rise public housing developments. With nearly half of the world's population living in urban areas, the unfolding trend is toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 14 publications
(22 reference statements)
1
46
1
3
Order By: Relevance
“…Thus, contrary to the findings of Yuen et al (2006), which revealed that households in Singapore were more willing to live on higher floors, residents in Kumasi metropolis are generally repulsive to high-rise living. Indeed, in the case of Singapore, the abovementioned study highlighted the high value attached to high-rise living, where households, owing to attractions such as, nice aerial view, privacy, etc., found reason in paying extra for higher floors (above 30 storeys).…”
Section: Discussioncontrasting
confidence: 54%
See 4 more Smart Citations
“…Thus, contrary to the findings of Yuen et al (2006), which revealed that households in Singapore were more willing to live on higher floors, residents in Kumasi metropolis are generally repulsive to high-rise living. Indeed, in the case of Singapore, the abovementioned study highlighted the high value attached to high-rise living, where households, owing to attractions such as, nice aerial view, privacy, etc., found reason in paying extra for higher floors (above 30 storeys).…”
Section: Discussioncontrasting
confidence: 54%
“…Vertical developments became a prominent feature of many cities in the twentieth century. Early conceptual development by Le Corbusier, and later by Wright and Soleri made a significant contribution to the development of highrise buildings in the early decades through to the middle part of the twentieth century (Wong 2004;Yuen et al 2006). The latter period of the century saw major advancement in construction technology, which together with booming population, urbanisation, and land scarcity, especially, in Asia, accelerated the development of high-rise buildings (Lee et al 2011;Mahgoub and Abbara 2011).…”
Section: Historical Context Of Vertical Developmentmentioning
confidence: 99%
See 3 more Smart Citations